Financial Stressors and Resources Associated With Financial Exploitation. Issue 2 (28th February 2022) - Hall, LaToya; Moray, Juno; Gross, Evan; Lichtenberg, Peter A
Abstract: Background and Objectives: The prevalence of older adult financial exploitation (FE) is increasing. Population-based survey estimates of FE in the older adult population range from 5% to 11%. Given the growing prevalence of FE victimization in older adult populations, understanding the population's vulnerability to FE has increased in importance. This study investigates a conceptual framework in an attempt to understand how financial stressors and resources are associated with substantiated FE in a sample consisting largely of Black older adults. Research Design and Methods: The study uses a cross-sectional design to investigate group differences among a total sample of 142 community-dwelling older adult participants, 62 of whom sought services to address FE and 80 with no history of FE. Results: The group of older adults who sought services to address FE was more likely to be unmarried and had fewer years of education. Measures of financial literacy and perceived financial vulnerability had protective and risk effects, respectively. Discussion and Implications: The present study found that sociodemographic and financial stress and resource measures have significant relationships with FE. These findings support the conceptual framework describing their relationship. This new conceptual framework provides a guiding factor in better understanding vulnerability to FE in older adults. The study also adds to the paucity of research completed on FE with Black older adults.